The autophagic inducer and inhibitor display different activities on the meiotic and developmental competencies of porcine oocytes derived from small and medium follicles - Chiyuki KOHATA-ONO; Takuya WAKAI; Hiroaki FUNAHASHI (The Society for Reproduction and Development, 2019)
This study aimed to examine the effect of rapamycin (autophagy inducer) and 3-methyladenine (3-MA, autophagy inhibitor) on the meiotic and developmental competencies of porcine oocytes derived from medium follicles (MF, 3-6 mm in diameter) and small follicles (SF, 1-2 mm in diameter) during in vitro maturation (IVM) process. The presence of 1 nM but not 10 nM rapamycin significantly increased the maturation rate of MF-derived oocytes (P < 0.05). However, the maturation rate of SF-derived oocytes was not affected by rapamycin at both concentrations (1 nM and 10 nM). The maturation rate of MF-derived oocytes decreased significantly (P < 0.05) in the presence of 0.2 mM but not 2 mM 3-MA than non-supplemented control. In contrast, in SF-derived oocytes, 3-MA at both 0.2 and 2 mM concentrations did not affect the maturation rates. The presence of 1 nM rapamycin significantly increased the blastocyst formation rate of MF-derived mature oocytes following parthenogenetic activation (P < 0.05). However, the blastocyst formation rate of SF-derived mature oocytes was not affected by the presence of rapamycin. The presence of 3-MA significantly reduced the blastocyst formation rate of MF-derived mature oocytes but did not change that of SF-derived oocytes. In conclusion, our study results show differences in activity of the autophagy inducer and inhibitor on the meiotic and developmental competencies of MF- and SF-derived porcine oocytes.